Volumen de agua almacenada en los árboles y su contribución a la conservación de los bosques de la Amazonía peruana. 2021 - Barbagelata Ramírez, Nélida (2023)
The objective of the research is to demonstrate the variation between the volume of water stored in trees and its contribution to the conservation of Amazonian forests. The population was made up of trees with DAP ≥ 10cm in 32 ha, distributed in high dry rod forests, high humid rods, intervened Arboretum el Huayo and primary forest of the Allpahuayo Mishana-RNAM National Reserve. The volume of water per tree was obtained using the formula for the difference of the total volume of the tree in the fresh state minus the volume of tree biomass. To define the state of forest conservation, values obtained from thirteen indicators were weighted: good, regular and bad. The results indicate a significant statistical difference in the volume of water in trees from the forests studied (Fc=7.551, p= 0.0007). There is greater variability in water volume in the upper and lower strata and less variability in the middle stratum. There is high variability of species and families in forests: high humid rodal (179 sp., 35 fam.), high dry rodal (130 sp, 35 fam.); intervened forest (131 esp., 32 fam); and primary forest (245 sp, 42 fam.). There is a direct relationship between the volume of water stored in trees and their contribution to conserving Amazonian forests: RNAM greater volume of water (200,984m3/ha) with good conservation status; high humid ridge (116,212m3/ha), high dry ridge (117,640m3/ha) and intervened forest (117,839 m3/ha) with a fair state of conservation.